Bias-bias Dikotomi dalam Buku Ajar Matakuliah Pendidikan Agama Islam di Perguruan Tinggi Umum - Hanafi, Yusuf (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
The kind of Islamic sciences being taught in many higher education institutes in Indonesia is that which tends to make students isolated from their world. These Islamic sciences in themselves are kind of separation from the religious and worldly, Islamic and secular. This dichotomous character had inflicted upon the students mentality, who in turn become equally dichotomous in their attitude, and way of thinking. This paper tries to explore this, and attempts to seek the best way in which the dichotomous curriculum can be replaced with the integrative one. It argues that, like the nature of Islam, religious sciences cannot be separated from the non-religious ones. The one must work hand in hand with the other so that. The paper addresses specifically the dilemmas intrinsic within the text book used by many higher religious institutes in the country called âReorientasi Pendidikan Islam: Menuju Pengembangan Kepribadian Insan Kamilâ. The bookâwe argueâdirects the students to adopt a single identity, disregarding therefore the multi and diverse racial, religious and even cultural background of the students. The paper is simply about a warning of the danger of the implication that the book can come up.